2016
DOI: 10.1371/journal.pone.0165912
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a Polymorphism (rs2910164) Predicts Colorectal Cancer Patients’ Susceptibility to Liver Metastasis

Abstract: miR-146a plays important roles in cancer as it directly targets NUMB, an inhibitor of Notch signaling. miR-146a is reportedly regulated by a G>C polymorphism (SNP; rs2910164). This polymorphism affects various cancers, including colorectal cancer (CRC). However, the clinical significance of miR-146a polymorphism in CRC remains unclear. A total of 59 patients with CRC were divided into 2 groups: a CC/CG genotype (n = 32) and a GG genotype (n = 27), based on the miR-146a polymorphism. cDNA microarray analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…17,18 Recently, abnormal miRNA expression profiles in multiple cancers including CRC have been reported by numerous studies. 19 According to several studies, the expression levels of miR-193a-5p and miR-146a-5p are substantially reduced in CRC 8,20 ; these findings were confirmed by the results of our study. In the present study, we observed that replacement of miR-193a-5p and miR-146a-5p individually and simultaneously in HT-29 CRC cell line reduced the ratio of MDM2 protein.…”
Section: Co-treatment With Mir-146a-5p and -193a-5p Significantly Supsupporting
confidence: 90%
“…17,18 Recently, abnormal miRNA expression profiles in multiple cancers including CRC have been reported by numerous studies. 19 According to several studies, the expression levels of miR-193a-5p and miR-146a-5p are substantially reduced in CRC 8,20 ; these findings were confirmed by the results of our study. In the present study, we observed that replacement of miR-193a-5p and miR-146a-5p individually and simultaneously in HT-29 CRC cell line reduced the ratio of MDM2 protein.…”
Section: Co-treatment With Mir-146a-5p and -193a-5p Significantly Supsupporting
confidence: 90%
“…For example, Iguchi et al observed colorectal cancer cell lines with the pre-miR-146a GG genotype exhibited significantly lower expression of miR-146a compared with those with the GC/CC genotype. [20] Yamashita et al proved proliferation, migration, and invasion abilities were significantly higher in human melanoma cell lines with the G allele than those with the C allele. [21] The study of Wang et al showed that individuals carrying the C allele had increased expression levels of miR-146a compared with those carrying the G allele.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that miR-146a is implicated in cell growth and metastasis in various cancers, of which the dysregulation of miR-146a is associated with pathological staging, poor differentiation and distant metastasis, acting as an independent prognostic element for overall survival in gastric cancer [ 25 , 26 ] and lung cancer [ 27 ]. In addition, miR-146a polymorphism rs2910164 is linked to the risk of esophageal cancer and colorectal cancers [ 28 , 29 ]. In this study, we analyzed the correlation of miR-146a with clinicopathologic characteristics and prognosis of OS patients, which indicated that increased expression of miR-146a was positively linked to tumor size and OS recurrence, but Kaplan-Meier analysis indicated that miR-146a was not an independent prognostic factor for overall survival and recurrence for OS patients, unveiling that miR-146a might be a potential biomarker for OS patients.…”
Section: Discussionmentioning
confidence: 99%